Right ventricular septal pacing via transmural approach for resynchronization in a child with postoperative heart block. Issue 10 (12th September 2020) - Carberry, Thomas; Hauck, Amanda; Backer, Carl; Webster, Gregory
Abstract: An infant with transposition of the great arteries was paced for postoperative heart block (single‐site, right ventricular [RV] epicardial). She developed severe left ventricular (LV) dysfunction and septal dyskinesis. Resynchronization was performed at the age of 4 with an LV epicardial lead and an RV septal endocardial lead. The endocardial lead was affixed to the interventricular septum, then tunneled through the RV free wall and attached to an abdominal pulse generator. QRS duration decreased (176 to 122 ms) and LV ejection fraction improved (26 to 61%) and remained stable for 8 years. We present a case of successful resynchronization in congenital heart disease using a transmural RV septal lead.